2013
DOI: 10.3109/2000656x.2013.823093
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic findings in breast reduction specimens

Abstract: Reduction mammaplasty is a commonly performed operation for treatment of breast hypertrophy. It allows examination of specimens from a seemingly healthy population. Although there are many publications reporting the incidence of occult breast carcinomas, only a few studies have specifically examined the incidence of other breast lesions in reduction mammaplasty specimens. The authors conducted a single-centre retrospective chart review examining the incidence of benign and precancerous lesions in breast reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…The importance of high-risk lesions for the patients is clear over time. 18 There are some limitations to our study. Because of its retrospective nature, we could not standardize preoperative routines and histopathological sampling.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The importance of high-risk lesions for the patients is clear over time. 18 There are some limitations to our study. Because of its retrospective nature, we could not standardize preoperative routines and histopathological sampling.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that routine histopathological analysis of reduction mammaplasty specimens is not costeffective because the incidence of occult cancers in the specimens is low. 1,37 However, as Kececi et al 18 suggested, these figures are usually calculated for individual cancers detected and do not consider risk-increasing findings. Highrisk lesions should be considered in determining whether histopathological analysis of specimens is cost-effective or not.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoma invasor foi encontrado em uma (0,25%) peça cirúrgica, de uma mulher de 51 anos submetida a cirurgia unilateral devida a mastectomia contralateral por câncer de mama, estando dentro da prevalência de carcinomas subclínicos (0 a 4%) publicados em outros trabalhos (9,10,11,19,21,23,24). Esta paciente também apresentava alterações proliferativas atípicas.…”
Section: Discussionunclassified
“…Na América Latina o índice de mortalidade por essa doença aumentou nos últimos quarenta anos (22). Em pacientes submetidas a mamoplastia redutora, a frequência de câncer diagnosticada nas peças cirúrgicas retiradas varia entre 0 a 4% (9,10,11,19,21,23,24).…”
Section: Câncer De Mamaunclassified